2022
DOI: 10.3847/2041-8213/ac947c
|View full text |Cite
|
Sign up to set email alerts
|

Panic! at the Disks: First Rest-frame Optical Observations of Galaxy Structure at z > 3 with JWST in the SMACS 0723 Field

Abstract: We present early results regarding the morphological and structural properties of galaxies seen with the James Webb Space Telescope (JWST) at z > 3 in the Early Release Observations toward the SMACS 0723 cluster field. Using JWST we investigate, for the first time, the optical morphologies of a significant number of z > 3 galaxies with accurate photometric redshifts in this field to determine the form of galaxy structure in the relatively early universe. We use visual morphologies and Morfometryka measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 63 publications
7
62
1
1
Order By: Relevance
“…This would be a surprising result in the pre-JWST era. However, recent JWST/ NIRCam morphological studies of the general galaxy population have shown that disk galaxies are already common at z > 1.5 (Ferreira et al 2022a(Ferreira et al , 2022bJacobs et al 2022). If star formation at z ≈ 1-3 mostly happens in disk galaxies, it can explain why our ALMA source hosts are mostly such systems.…”
Section: Disk Galaxy Evolutionmentioning
confidence: 90%
“…This would be a surprising result in the pre-JWST era. However, recent JWST/ NIRCam morphological studies of the general galaxy population have shown that disk galaxies are already common at z > 1.5 (Ferreira et al 2022a(Ferreira et al , 2022bJacobs et al 2022). If star formation at z ≈ 1-3 mostly happens in disk galaxies, it can explain why our ALMA source hosts are mostly such systems.…”
Section: Disk Galaxy Evolutionmentioning
confidence: 90%
“…To within the current uncertainties, these conclusions are not unique, but they may point to the need for a more significant fraction of red spiral galaxies at 3.4-4.5 μm, as other recent JWST work has suggested (e.g., Ferreira et al 2022;Fudamoto et al 2022). With the new NIRCam images now at hand, future IGL models may need to include a larger fraction of (dusty) spirals.…”
Section: Discussionmentioning
confidence: 67%
“…Yet, not all of these galaxies are ellipticals, as discussed below. As the beautiful first NIRCam images already attest, JWST images will thus see a greater dominance of, and emphasis on, earliertype galaxies, which will stand out the most in JWST images (e.g., Ferreira et al 2022). This is in contrast to the "Faint Blue Galaxy" population of actively star-forming galaxies that have dominated HST's UV-optimally images for the past decades (e.g., Driver et al 1995;Abraham et al 1996;Windhorst et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations